Transformative adaptation as a sustainable response to climate change: insights from large-scale case studies - Filho, W.L. (Springer Science and Business Media B.V., 2022)
Many climate change responses focus on form rather than substance. As a result, they invariably look at the consequences but ignore the drivers of climate change. Since past approaches towards climate change adaptation have had limited success, the most effective and sustainable way to minimize future climate change impacts on humanity is through transformative adaptation (TA). This paper defines and characterizes the conceptual foundations of this term and outlines how TA influences current and future climate change adaptation challenges. This paper reviews the meaning and purpose of transformation in climate change adaptation and, by means of a set of case studies, explains how their commonalities can help define good TA practice. Deploying a range of situations, this study shows how this approach is being implemented in a set of countries, and considers its potential transformative impact, its benefits, and challenges. The results obtained have shown that when implemented with due care, TA can yield long-term benefits to local communities. The paper conclude by listing some measures by which TA may be further deployed as a means of helping communities to meet the future challenges posed by a changing climate. Â© 2022, The Author(s), under exclusive licence to Springer Nature B.V.